Exponentiated Gamma Distribution: Different Methods of Estimations. (13th March 2012) - Shawky, A. I.; Bakoban, R. A.
Abstract : The exponentiated gamma (EG) distribution and Fisher information matrices for complete, Type I, and Type II censored observations are obtained. Asymptotic variances of the different estimators are derived. Also, we consider different estimators and compare their performance through Monte Carlo simulations.